A middle infrared hyperspectral imaging based on diffraction grating and metalens - Gong, Tu (Nanyang Technological University, 2023)
Hyperspectral imaging is increasingly important in modern life, and it can be applied in many areas, such as molecular biology, remote sensing, and biomedical imaging. The metalens can reduce the size of hyperspectral imaging systems by replacing the dispersive and focusing lens. Meanwhile, it can perform the better chromatic correction. Metalens based on germanium (Ge) and silicon (Si) materials is designed and simulated for a diffraction grating. It can be a dispersive element in hyperspectral imaging for light in the mid-infrared region (MIR). The diffraction grating style is improved from blazed grating by changing the ladder or cylindrical surfaces to several bars. This design can simplify the fabrication process and hence reduce the cost. 0.457 is the highest transmission achieved for germanium material when the period is 2.82 μm and the height is 1.36 μm. Meanwhile, 0.336 is the highest transmission obtained for the silicon material when the grating period is 1.4 μm and the height is 3.05 μm. However, a Ge-based metalens with a 2.9 μm grating period and 4.03 μm height is selected as the final design because it has relatively high transmission and shows a broader wavelength range. Additionally, a simulation of a meta-diffraction grating for visible light is made based on relevant papers to enhance the understanding of meta-diffraction grating and familiarity with the simulation software. In the future, achromatic metalens can be used for the focusing lens of hyperspectral imaging, which can be combined with the designed dispersive metalens to achieve better performance.